(3GdETGQI aj Yde GdYHGQIs - (3LdGd GdOjf YHO Gddg Hf SdjeGf Hf MGRe GdeRis; (3YHO Gddg Hf SdjeGf Hf MGRe GdeRj, LdGd GdOjfs
(3ChdgG (B:s
(3hHYO ,aGfg deG eqf Gddg JYGdi Ydqi HJCdja cJGH YeOI GdJMQjQ ai Yde GdJYHjQ JJHYJ ajg bhGYO GdYde heHGfjg s
(3BNQgG (B:s
(3hef QCi Cfg LeY Hjf fhYjf ef GdMjhGf cGdMeGe hGdZQHGf hGdfYGL aEfg jbhO adjJb Gddg QHg hdjfJg s
(3GNJUQg ef cJGHg GdcHjQ YeOI GdJMQjQ ai Yde GdJYHjQ hQJHg Ydi GQHYjf HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3JYHjQ GdQDjGs